2022
DOI: 10.1007/s10107-021-01756-6
|View full text |Cite
|
Sign up to set email alerts
|

Error bounds and a condition number for the absolute value equations

Abstract: Due to their relation to the linear complementarity problem, absolute value equations have been intensively studied recently. In this paper, we present error bound conditions for absolute value equations. Along with the error bounds, we introduce a condition number. We consider general scaled matrix p-norms, as well as particular p-norms. We discuss basic properties of the condition number, including its computational complexity. We present various bounds on the condition number, and we give exact formulae for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Under the condition that AVEs (4) has a unique solution, ref. [16] conducted a study on the error bound and condition number of AVEs (4), which play crucial roles for the convergence analysis of AVEs (4). Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Under the condition that AVEs (4) has a unique solution, ref. [16] conducted a study on the error bound and condition number of AVEs (4), which play crucial roles for the convergence analysis of AVEs (4). Ref.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze theoretical properties and effectively solve the AVE, many sufficiency conditions on solvability and numerical calculation methods were studied in [1,5,[7][8][9][10][11][12]. As described in [1], the general NP-hard LCP subsuming many nonlinear optimization problems can be equivalent to an AVE.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [16] showed the SOR-like strategy with optimal parameters and examined some novel convergence situations different from [15]. Zamani and Hladík [17] offered a new concave minimization approach for AVE (1), which addresses the deficiency of the system proposed in [18] and others (see [19][20][21][22][23]).…”
Section: Introductionmentioning
confidence: 99%